The Development of Teaching Aids Through Websites for Basketball 1 Course - Sungkaphan, Siriwan (Academic Journal of Thailand National Sports University, 2013)
The objectives of this study were to investigate the effectiveness of Internet-based Lessons in Basketball 1 Course, compare and contrast learning achievement in Basketball 1 Course and Pre and Post Teaching through internet, compare and contrast learning achievement of in Basketball 1 Course between internet-based learning group and typical lecturing learning group and review students' satisfaction of internet-based lessons in Basketball 1 Course. Participants in this study included 35 specific randomized undergraduate students enrolling in Basketball 1 course during the second semester, academic year 2553 B.E., physical education major, faculty of education, Suphanburi Institution of Physical Education The process of developing internet-based instructional media in Basketball 1 Course consisted of content determination, content analysis as subunits, determining behavioral objective and developing 120 item assessment test to measure student's learning achievement. Qualitative criterions were measured in term of Index of Consistency, Index of Item Objective Consistency (IOC) between 0.67-1.00, difficulty index (p) between 0.23-0.80, Discrimination (r) between 0.20-0.80 and Index of Confidence (KR-20) equaled to 0.85. Further to the findings, it was concluded as the following Effectiveness analysis of internet-based lessons in Basketball 1 Course showed that the effectiveness of computer based lessons (E,/E,) was 85.43783.50 as much as determined criteria at 80/80 Students' learning achievement through internet-based lessons of Basketball 1 course showed significantly increased statistically post learning achievement with p.05 Students in internet-based learning group had got higher learning achievement than typical learning group. Students were highly satisfied with internet-based lessons in Basketball 1 Course.